Phonology: Tool for Poetic Analysis - Tumbahang, Mohan Kumar (JODEM: Journal of Language and Literature, 2019)
This article aims to focus on how the linguistic sound patterns can be a significant tool in literary analysis specifically in the analysis of the literary genre poetry. It attempts to discuss about the crucial points for successful poetic analysis through linguistic sounds which is technically termed as phonemes. To deal with this issue, the article writer has formed a mindset to avail the qualitative research method or the study is based on non-numerical data. The method being the qualitative one, the library consultation and empirical insight are a must. It is fairly expected that the article can be of certain help to the language learners, language teachers, critics, course designers and planners of teaching materials. The article has drawn the conclusion that phonology can be significant means for interpreting the poetic text. The poetic texts/discourses can be analyzed in terms of the frequency of certain sounds’ recurrence. In other words, prosody, tone (author’s attitude), and verse types can be analyzed through the linguistic sound pattern.